Accumulation of Pol Mutations Selected by HLA-B*52:01-C*12:02 Protective Haplotype-Restricted Cytotoxic T Lymphocytes Causes Low Plasma Viral Load Due to Low Viral Fitness of Mutant Viruses - Murakoshi, Hayato (J Virol, 2017)
HLA-B*52:01-C*12:02, which is the most abundant haplotype in Japan, has a protective effect on disease progression in HIV-1-infected Japanese individuals, whereas HLA-B*57 and -B*27 protective alleles are very rare in Japan. A previous study on HLA-associated polymorphisms demonstrated that the number of HLA-B*52:01-associated mutations at four Pol positions was inversely correlated with plasma viral load (pVL) in HLA-B*52:01-negative individuals, suggesting that the transmission of HIV-1 with these mutations could modulate the pVL in the population. However, it remains unknown whether these mutations were selected by HLA-B*52:01-restricted CTLs and also reduced viral fitness. In this study, we identified two HLA-B*52:01-restricted and one HLA-C*12:02-restricted novel cytotoxic T-lymphocyte (CTL) epitopes in Pol. Analysis using CTLs specific for these three epitopes demonstrated that these CTLs failed to recognize mutant epitopes or more weakly recognized cells infected with mutant viruses than wild-type virus, supporting the idea that these mutations were selected by the HLA-B*52:01- or HLA-C*12:02-restricted T cells. We further showed that these mutations reduced viral fitness, although the effect of each mutation was weak. The present study demonstrated that the accumulation of these Pol mutations selected by HLA-B*52:01- or HLA-C*12:02-restricted CTLs impaired viral replication capacity and thus reduced the pVL. The fitness cost imposed by the mutations partially accounted for the effect of the HLA-B*52:01-C*12:02 haplotype on clinical outcome, together with the effect of HLA-B*52:01-restricted CTLs on viral replication, which had been previously demonstrated. IMPORTANCE Numerous population-based studies identified HLA-associated HIV-1 mutations to predict HIV-1 escape mutations from cytotoxic T lymphocytes (CTLs). However, the majority of these HLA-associated mutations have not been identified as CTL escape mutations. Our previous population-based study showed that five HLA-B*52:01-associated mutations at four Pol positions were inversely correlated with the plasma viral load in HLA-B*52:01-negative Japanese individuals. In the present study, we demonstrated that these mutations were indeed selected by CTLs specific for novel B*52:01- and C*12:02-restricted epitopes and that the accumulation of these mutations reduced the viral fitness in vitro. This study elucidated the mechanism by which the accumulation of these CTL escape mutations contributed to the protective effect of the HLA-B*52:01-HLA-C*12:02 haplotype on disease progression in HIV-1-infected Japanese individuals.